Serum fructosamine and glycemic status in the presence of the sickle cell mutation. (July 2021) - Doumatey, Ayo P.; Feron, Hermon; Ekoru, Kenneth; Zhou, Jie; Adeyemo, Adebowale; Rotimi, Charles N.
Abstract: Aims: The glycated hemoglobin (HbA1c) test can be unreliable in the presence of hemoglobinopathies. The co-existence of type 2 diabetes (T2D) with sickle cell anemia calls for alternative tests. Therefore, we established a reference interval for serum fructosamine and evaluated its utility as a potential glycemic biomarker that is not affected by abnormal hemoglobin. Methods: The accuracies of serum fructosamine in monitoring and diagnosing T2D were evaluated using the Area under the Receiver Operating Characteristics and other measures in 618 Nigerians with or without sickle cell trait. The estimated diagnostic cut-off for serum fructosamine was then validated in an independent multi-ethnic cohort of 634 West Africans. Results: Serum fructosamine was similar between individuals with or without sickle cell trait (median: 287 vs 275 umol/L, p = 0·11, respectively) despite statistically different HbA1c. Fructosamine was highly correlated with both HbA1c and fasting glucose independently of sickle cell trait. The areas under the curve (AUC) of serum fructosamine in identifying individuals with uncontrolled glycemia and individuals with T2D were similar and independent of sickle cell trait: 0·92 (95% confidence interval [95% CI ], 0·88-0·95 and 0.92 (95% CI, (0.89–0.95) respectively. Conclusions: Serum fructosamine is a good alternative to HbA1c for monitoring and diagnosing T2D in the presence of sickle cell trait.